A novel EEG marker predicts perceived sleepiness and poor sleep quality. Issue 5 (4th March 2022) - Lechat, Bastien; Hirotsu, Camila; Appleton, Sarah; Younes, Magdy; Adams, Robert J; Vakulin, Andrew; Hansen, Kristy; Zajamsek, Branko; Wittert, Gary; Catcheside, Peter; Heinzer, Raphael; Eckert, Danny J
Abstract: Study Objectives: To determine if a novel EEG-derived continuous index of sleep depth/alertness, the odds ratio product (ORP), predicts self-reported daytime sleepiness and poor sleep quality in two large population-based cohorts. Methods: ORP values which range from 0 (deep sleep) to 2.5 (fully alert) were calculated in 3s intervals during awake periods (ORPwake ) and NREM sleep (ORPNREM ) determined from home sleep studies in the HypnoLaus ( N = 2162: 1106 females, 1056 males) and men androgen inflammation lifestyle environment and stress (MAILES) cohorts ( N = 754 males). Logistic regression was used to examine associations between ORPwake, ORPNREM, and traditional polysomnography measures (as comparators) with excessive sleepiness (Epworth sleepiness scale >10) and poor sleep quality (Pittsburgh sleep quality index >5) and insomnia symptoms. Results: High ORPwake was associated with a 30% increase in poor sleep quality in both HypnoLaus (odds ratio, OR, and 95% CI) 1.28 (1.09, 1.51), and MAILES 1.36 (1.10, 1.68). High ORPwake was also associated with a 28% decrease in excessive daytime sleepiness in the MAILES dataset. ORPNREM was associated with a 30% increase in poor sleep quality in HypnoLaus but not in MAILES. No consistent associations across cohorts were detected using traditional polysomnography markers. Conclusions: ORP, a novel EEG-derived metric, measured during wake periods predicts poor sleep quality in two independent cohorts. Consistent with insomnia symptomatology of poor perceived sleep in the absence of excessive daytime sleepiness, ORPwake may provide valuable objective mechanistic insight into physiological hyperarousal.